Exclusive Maternal Milk Compared With Exclusive Formula on Growth and Health Outcomes in Very-Low-Birthweight Preterm Infants: Phase II of the Pre-B Project and an Evidence Analysis Center Systematic Review - Taylor, Sarah N.; Fenton, Tanis R.; Groh-Wargo, Sharon; Gura, Kathleen; Martin, Camilia R.; Griffin, Ian J.; Rozga, Mary; Moloney, Lisa (Frontiers in Pediatrics, 2022)
As part of the Pre-B Project, a systematic review was conducted to evaluate associations between exclusive maternal milk (greater than or equal to 75%) intake vs. exclusive formula intake and growth and health outcomes in very low birthweight (VLBW) preterm infants. The protocol from the Academy of Nutrition and Dietetics Evidence Analysis Center and the PRISMA checklist were followed. Thirteen observational studies were included; 11 studies reported data that could be synthesized in pooled analysis. The evidence is very uncertain (very low quality) about the effect of exclusive maternal milk on all outcomes due to observational study designs and risk of selection, performance, detection, and reporting bias in most of the included studies. Very low-quality evidence suggested that providing very low birthweight preterm infants with exclusive maternal milk was not associated with mortality, risk of necrotizing enterocolitis, sepsis, or developing bronchopulmonary dysplasia compared to exclusive preterm formula, but exclusive maternal milk was associated with lower risk of retinopathy of prematurity (very low certainty). Results may change when additional studies are conducted. There was no difference in weight, length and head circumference gain between infants fed fortified exclusive maternal milk and infants receiving exclusive preterm formula, however, weight and length gain were lower in infants fed non-fortified exclusive maternal milk. Given the observational nature of human milk research, cause-and-effect evidence was lacking for VLBW preterm infants. Registered: PROSPERO ID CRD42018086829